2023
DOI: 10.1111/jvim.16618
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐base imbalances and the association of blood‐gas variables, electrolytes, and biochemical analytes with outcome in hospitalized calves undergoing abdominal surgery

Abstract: Background Surgical abdominal emergencies in calves are associated with a guarded prognosis and have the potential for complex metabolic derangements including acid‐base imbalances. Objectives To perform a comprehensive analysis of acid‐base status and to assess the prognostic relevance of preoperative clinicopathologic variables in calves undergoing abdominal surgery. Animals Hospital‐based study samples of 535 (dataset 1; DS1) and 83 calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…29 In disease conditions characterized by pronounced metabolic changes, negative values for the calculated USI and SIG indicate the presence of unidentified anions often correlate with negative outcomes of the disease. 23,25,30,31 Median USI and SIG values in our study were within the normal limits for healthy and diseased calves diagnosed with TUS and in groups based on categorizing TUS and WISC score. The statistical differences were found in calves with ultrasonographic lung consolidations, which paradoxically had higher mean values than healthy calves.…”
Section: Categorizationssupporting
confidence: 57%
See 3 more Smart Citations
“…29 In disease conditions characterized by pronounced metabolic changes, negative values for the calculated USI and SIG indicate the presence of unidentified anions often correlate with negative outcomes of the disease. 23,25,30,31 Median USI and SIG values in our study were within the normal limits for healthy and diseased calves diagnosed with TUS and in groups based on categorizing TUS and WISC score. The statistical differences were found in calves with ultrasonographic lung consolidations, which paradoxically had higher mean values than healthy calves.…”
Section: Categorizationssupporting
confidence: 57%
“…In WISC 5 /TUS 1cm and WISC 5 /TUS 3cm categorizations, there was a clear difference between calves with and without lung consolidations detected by TUS, although, the abnormalities found were usually not beyond the normal reference ranges (see Table 2). Overall, these results suggest that metabolic changes during an episode of BP diagnosed with WISC score or by TUS set at ≥1 or ≥3 cm were less critical than other disease conditions characterized by severe disarrangements, such as abdominal surgical emergencies and diarrhea in calves 23,25 or severe mastitis and acute diarrhea in goats, 26 which were characterized by clinicopathologic imbalances and alterations in acid‐base status exceeding the reference ranges. Our results agree with previous observations, 10 which showed that in calves with BP the overall effects on base‐acid balance were of mild to moderate magnitude.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This interpretation is corroborated by the higher Crea levels in non-survivors when compared with survivors, as well as higher Hct, Hb, and RBC values in non-survivors compared with survivors. Urea was also found to be a better predictor of a postoperative outcome when compared with Crea in calves, according to a recent study [ 28 ]. Serum urea is considered to be more sensitive for the diagnosis of dehydration, as elevated values are the result of increased renal tubular reabsorption and decreased renal glomerular filtration, while elevated Crea are only the result of decreased renal glomerular filtration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%